DAYA DUKUNG KESUBURAN TANAH PUCUK SEBAGAI MATERIAL REKLAMASI DI TANJUNG BARU DESA BAKONG KECAMATAN SINGKEP BARAT KABUPATEN LINGGA - Aji, Ananto (Jurnal Geografi, 2013)
This study aimed to determine the capability of top soil fertility which will becuted from mining area and will be used as main material in land reclamation.This research conducted in term that there will be mining activity in TanjungBaru, Bakong Village, Singkep Barat District, Lingga Regency of Riau Province,with total area 106.62 ha. The mining activity will cut the top soil 5,608,643 m3or equal to 6,730,372 ton of soil. The cutted soil will used to be main material ofland reclamation and become a substrat for revegetation plants. The resultshowed that the capacity of study field soil fertility was categorized as very low tolow. In order to preserve the soil condition, it must be properly stored. Therecommendation from this research is, it needs to re-analysis of soil conditionbefore used to revegetation in order to test the land fertility status, and as thebasic for determine the fertilizer dose that can be applied.